Altered gut microbiome in FUT2 loss-of-function mutants in support of personalized medicine for inflammatory bowel diseases. (20th September 2021) - Cheng, Sijing; Hu, Jun; Wu, Xianrui; Pan, Ji-An; Jiao, Na; Li, Yichen; Huang, Yibo; Lin, Xutao; Zou, Yifeng; Chen, Yuan; Zhu, Lixin; Zhi, Min; et al.
Abstract: The FUT2 loss-of-function mutations are highly prevalent and are associated with inflammatory bowel disease (IBD). To investigate the impact of FUT2 loss-of-function mutation on the gut microbiota in patients with IBD, 81 endoscopically confirmed IBD patients were genotyped and divided into 3 groups: homozygous for functional FUT2 genes ( SeSe ), with one copy of non-functional FUT2 gene ( Sese ), or homozygous for non-functional FUT2 genes ( sese ). Escherichia, which attaches to fucosylated glycoconjugates, was the only abundant genus exhibiting decreased abundance in sese patients. Compared with SeSe or Sese patients, sese patients exhibited higher abundance in CD8 + inducing Alistipe and Phascolarctobacterium and Th17 inducing Erysipelotrichaceae UCG-003. Counter-intuitively, butyrate-producing bacteria were more abundant in sese patients. Consistently, metabolomics analysis found higher levels of butyrate in sese patients. Our data support the hypothesis that FUT2 loss-of-function mutation participates in the IBD pathogenesis by decreasing binding sites for adherent bacteria and thus altering the gut microbiota. Decreased abundances of adherent bacteria may allow the overgrowth of bacteria that induce inflammatory T cells, leading to intestinal inflammation. As FUT2 loss-of-function mutations are highly prevalent, the identification of T cell inducing bacteria in sese patients could be valuable for the development of personalized microbial intervention for IBD.